Strength Characteristics of Alkali-Activated Slag Mortars with the Addition of PET Flakes - Agnieszka Kocot (MDPI AG, 2021)
The production of ordinary Portland cement is associated with significant CO2 emissions. To limit these emissions, new binders are needed that can be efficiently substituted for cement. Alkali-activated slag composites are one such possible binder solution. The research programme presented herein focused on the creation of alkali-activated slag composites with the addition of PET flakes as a partial substitute (5%) for natural aggregate. Such composites have a significantly lower impact in terms of CO2 emissions in comparison to ordinary concrete. The created composites were differentiated by the amount of activator (10 and 20 wt.%) and curing temperature (from 20 to 80 °C). Their mechanical properties were tested, and a scanning electron microscope analysis was conducted. Compressive and flexural strengths ranging from 29.3 to 68.4 MPa and from 3.5 to 6.1 MPa, respectively, were achieved. The mechanical test results confirmed that a higher amount of activator improved the mechanical properties. However, the influence of the PET particles on the mechanical properties and microstructure varied with the curing temperature and amount of activator. Areas that require further research were identified.